(untitled) (Research, Society and Development, 2021)
Introduction: The prolonged use of proton pump inhibitors has become common and has been widely applied in the treatment of these various gastrointestinal diseases and studies have shown a possible relationship between the use of these drugs and histopathological changes in the gastric region. Objective: To understand the possible relationship between the use of proton pump inhibitors (PPIs) and gastric disorders. Methodology: For this, the descriptors in the Bireme, Pubmed, Scielo databases were applied, considering the studies of the last 16 years. Expected results: The studies are expected to answer our questions and serve as a basis for further studies to be carried out. Conclusion: About the possible relationship between the use of proton pump inhibitors and cancer, it is important to emphasize that, with continuous use and in long-term therapy, this class of drug triggered hypergastrinemia in a large majority of patients and a high incidence of ECL cell hyperplasia. Regarding its association with H. pylori, positive patients who had been treated with PPIs for a long period had an increased risk of body atrophy compared to patients who were negative for Hp. Finally, there was no evidence of the association of PPIs with the induction or elevation of those rich in cancer.